(untitled) (Journal of Applied Learning and Teaching, 2025)
This study explores teachers’ perceptions and practices of green pedagogies in fostering eco-literacy among students across diverse educational contexts in Africa, Europe, and Asia. Data were collected from an online questionnaire completed by 90 university educators from various disciplines, and we employed an interpretivist research approach. Thematic analysis revealed five key areas: definitions and understanding of green pedagogies, practical implementation strategies, fostering active citizenship, emotional impacts of eco-education, and perceived effectiveness of these approaches. Findings highlight that educators recognize the necessity of integrating sustainability into curricula and actively employ innovative methods, such as project-based learning and outdoor exploration, to engage students. However, challenges, including an exam-oriented culture and resource limitations, impede effective implementation. This research contributes significantly to the literature on environmental education, shedding light on teachers’ perspectives that have been historically overlooked. It emphasizes the need for enhanced professional development and institutional support to cultivate eco-literacy, promoting responsible environmental citizenship in an increasingly complex global landscape. The insights gained from this study offer actionable strategies for educators and policymakers, reinforcing the importance of embedding eco-literacy within educational frameworks. These insights could inform the design of targeted professional development programs to enhance eco-literacy.